2015
DOI: 10.1007/s11105-015-0853-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Asteraceae Chloroplast Genomes: Structural Organization, RNA Editing and Evolution

Abstract: Comparative chloroplast genome analysis presents new opportunities for performing molecular phylogeny studies and revealing the significant evolutionary features in higher plants, which has been widely documented from conifers to grass family. However, a systematic analysis of chloroplast genomes in Asteraceae family has not been conducted up to now. In this study, we compared and analyzed the gene content, genomic organization, and RNA editing sites of eight representative Asteraceae chloroplast genomes. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 29 publications
6
61
0
Order By: Relevance
“…The ψycf1 gene was located at the junction between SSC and IRb. This pattern of IR expansion and contraction of partial copies of non-coding genes is a common occurrence in most terrestrial species [66]. These outcomes can provide insight into the evolutionary processes of chloroplast genomes, as well as being a source of DNA barcodes.…”
Section: Ir Expansion and Contractionmentioning
confidence: 91%
“…The ψycf1 gene was located at the junction between SSC and IRb. This pattern of IR expansion and contraction of partial copies of non-coding genes is a common occurrence in most terrestrial species [66]. These outcomes can provide insight into the evolutionary processes of chloroplast genomes, as well as being a source of DNA barcodes.…”
Section: Ir Expansion and Contractionmentioning
confidence: 91%
“…Since Palmer (1983) originally documented this phenomenon in Phaseolus vulgaris , it has been confi rmed in a wide variety of plant species ( Palmer, 1985 ), including algae ( Aldrich et al, 1985 ;Bourne et al, 1992 ;Linne von Berg and Kowallik, 1992 ;Cattolico et al, 2008 ) and ferns ( Stein et al, 1986 ), and is now a well-accepted feature of chloroplast genomes (e.g., Heinhorst and Cannon, 1993 ;Doyle and Doyle, 1999 ). Nonetheless, this phenomenon has been overlooked in several recent analyses that have evaluated the orientation of the SSC region a phylogenetic context (e.g., Ibrahim et al, 2006 ;Yang et al, 2010 ;Liu et al, 2013 ;Walker et al, 2014 ;Zhang et al, 2014 ;Wang et al, 2015 ). Th ese analyses compare the SSC orientation among lineages using a single plastome to represent each lineage and thus have missed the withinindividual variation that exists in this region.…”
mentioning
confidence: 99%
“…For example, two sequences of Lactuca sativa that have been independently published (NC_007578 and DQ_383816) were entered with diff erent orientations of the SSC region, which could be interpreted as a major inversion existing within the species if the investigators are not aware that two isomers naturally exist (e.g., Walker et al, 2014 ). Th is misinterpretation has now occurred in several studies (e.g., Ibrahim et al, 2006 ;Yang et al, 2010 ;Liu et al, 2013 ;Walker et al, 2014 ;Zhang et al, 2014 ;Wang et al, 2015 ), leading to the hypothesis that the SSC region is an inversion "hotspot" ( Liu et al, 2013 ). Experiments that attempted to use PCR to allegedly confi rm a single orientation of the SSC region within samples have likely perpetuated this misconception (e.g., Nie et al, 2012 ;Liu et al, 2013 ).…”
mentioning
confidence: 99%
“…The most parsimonious interpretation of our results suggests that structural heteroplamsy should be extremely common across all angiosperms. In light of this, it may be necessary to re-examine many previous suggestions of structural differences in the chloroplast genomes of angiosperms between species (9-13), as Emery et al (14) suggested. For example, Ibrahim et al (9) implied that the SSC of Gossypium barbadense was inverted when compared to Gossypium hirsutum .…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of chloroplast genome structural heteroplasmy is important for a number of reasons. First, some recent papers have suggested that the orientation of the single copy regions differ between species (9-13), but Emery et al (14) pointed out that these studies seem to have overlooked the possibility that both orientations may coexist in a single individual. Second, the relationship between the structure of the chloroplast genome and the existence or otherwise of structural heteroplasmy remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%